Remodeling the cancer epigenome: mutations in the SWI/SNF complex offer new therapeutic opportunities. Issue 5 (4th May 2019) - Orlando, Krystal A; Nguyen, Vinh; Raab, Jesse R; Walhart, Tara; Weissman, Bernard E
ABSTRACT: Introduction : Cancer genome sequencing studies have discovered mutations in members of the SWItch/Sucrose Non-Fermentable (SWI/SNF) chromatin-remodeling complex in nearly 25% of human cancers. The SWI/SNF complex, first discovered in S. cerevisiae, shows strong conservation from yeast to Drosophila to mammals, contains approximately 10–12 subunits and regulates nucleosome positioning through the energy generated by its ATPase subunits. The unexpected finding of frequent mutations in the complex has fueled studies to identify the mechanisms that drive tumor development and the accompanying therapeutic vulnerabilities. Areas covered : In the review, we focus upon the potential roles different SWI/SNF subunit mutations play in human oncogenesis, their common and unique mechanisms of transformation and the potential for translating these mechanisms into targeted therapies for SWI/SNF-mutant tumors. Expert opinion : We currently have limited insights into how mutations in different SWI/SNF subunits drive the development of human tumors. Because the SWI/SNF complex participates in a broad range of normal cellular functions, defining specific oncogenic pathways has proved difficult. In addition, therapeutic options for SWI/SNF-mutant cancers have mainly evolved from high-throughput screens of cell lines with mutations in different subunits. Future studies should follow a more coherent plan to pinpoint common vulnerabilities among these tumors. Trial registration: ClinicalTrials.gov identifier: NCT02601937. Trial registration: ClinicalTrials.gov identifier: NCT02601950. Trial registration: ClinicalTrials.gov identifier: NCT03213665. Trial registration: ClinicalTrials.gov identifier: NCT02059265.